Science of writing for publication in scientific journals: steps and resources - Shah, Jay Narayan (Journal of Patan Academy of Health Sciences, 2020)
The step-by-step process on how to write a publishable manuscript, starting from the title up to the reference requires reading articles and books which are available in plenty online and offline on scientific writing, prepare to start the journey of writing and publication in scientific journals. One of the best ways to embark on this journey is by trying to do it, by practice, practice, and more practice.Historically, the initiation of modern scientific writing began some 350 years ago in 1665 with the publication of ‘Philosophical Transactions’, considered as one of the first scientific journal.1,2 Half a century later, the format of writing and peer-review were introduced in 1731, but it took almost two centuries, until after World War II, for the wider acceptance of the concept by the journals.3 The structured format of writing introduced in the 1940s has evolved to what we know today as IMRAD- introduction-methods-results-and-discussion. This IMRAD format helps guide authors to address the essential components of research work, and makes it easier for the reviewer, the editors, and most importantly the readers to understand what is being presented.4 The IMRAD, and aIMRAD (a=abstract, in which the discussion is replaced and presented as conclusion) is an easy concept for comprehension, Figure 1.5